Improved Protodyakonov’s Method of the Tunnel Surrounding Rock Pressure under the Seepage Condition of Weak Interlayer - Jing Hu; Jiafeng Xiao; Zhuanyun Yang; Peng Xie; Haijia Wen (Geofluids)
A reasonable support scheme is the main factor to be considered when constructing tunnels, and it is essential to accurately calculate the surrounding rock pressure of tunnels. This work focuses on the improved method used to calculate the surrounding rock pressure of a tunnel affected by the seepage of its weak interlayer. Based on Protodyakonov’s theory, the simulation result obtained by finite difference method is adopted to determine the modified Protodyakonov’s method (MPM) used to calculate the surrounding rock pressure of the tunnel taking the angle and position of its interlayer as the entry point. To confirm the efficacy of the MPM, used for a Chongqing Mountain tunnel affected by the seepage of its weak interlayer, the other two normal calculation methods were compared with the MPM and field monitoring results. It is shown that the calculated results of the MPM are closer to those of the field monitoring. MPM meets the requirements of support strength and can be used as a reference to calculate the surrounding rock pressure of tunnels affected by the seepage of a weak interlayer.